The forest incentive policy in argentina. Case-study: Santiago del Estero - De Renolfi, M.C.=700 1 Ortuño Perez, S.F.
(Es, En)
ilus., 32 ref.
Keywords: POLITICA FORESTAL; REFORESTACION; SUBSIDIOS; ECONOMIA; ARGENTINA; ECONOMIA FORESTAL